Lactate increases tumor malignancy by promoting tumor small extracellular vesicles production via the GPR81-cAMP-PKA-HIF-1α axis - Luo, Man; Zhu, Junqi; Ren, Jie; Tong, Yuxiao; Wang, Limin; Ma, Shenglin; Wang, Jiaoli (Frontiers in Oncology, 2022)
Lactate and tumor cell-derived extracellular vesicles (TEVs) both contribute to tumor progression. However, it is still unclear whether lactate can accelerate tumor development by directly promoting TEV production. Here, we show that lactate decreases intracellular cAMP levels and subsequent PKA activation via GPR81, which inhibits the PKA-induced ubiquitination of HIF-1α that causes degradation. Then, the HIF-1α-mediated transcription of Rab27a is enhanced, leading to increased TEV release. In this way, lactate promotes lung metastasis by murine melanoma. In addition, we show that serum lactate levels are positively correlated with serum EV levels and Rab27a and HIF-1α protein levels in the tumor tissues of lung cancer patients. Thus, our results reveal a novel mechanism underlying lactate-mediated tumor progression induced by TEVs and provide new strategies for tumor therapy.